ANALISIS STRATEGI MATHEMATICAL HABITS OF MIND SISWA DALAM PEMECAHAN MASALAH MATERI SPLTV - Dewi Kartika Sari; Zubaidah R.; Romal Ijuddin (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine and describe mathematical habits of mind strategies in solving problems of students with high and low mathematical abilities on the material of three variable linear equation systems in Senior High School 7 Pontianak. The research method used in this research is descriptive with a case study research form. The subjects in this study were students of class XI MIPA 3 in Senior High School 7 Pontianak and the interview subjects were two students with high math ability and two subjects with low math ability. The results showed that students with high mathematical abilities meet all components of mathematical habits of mind strategies, namely exploring mathematical ideas, generalizing, reflecting on the correctness of answers, identifying problem solving strategies that can be applied to broader problems, making questions and making examples. Students with low mathematical abilities meet three components of mathematical habits of mind strategies, namely generalizing, identifying problem solving strategies that can be applied to broader problems, and making questions.Keywords : Mathematical Habits Of Mind, Analysis, Problem Solving